2021
DOI: 10.2172/1823119
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Wind Resilience Metrics for Electric Energy Delivery Systems: Comprehensive Literature Review

Abstract: W hile most people have a general concept of what it means to be "resilient, " an examination of definitions from different sources reveals that there are key commonalities, but key differences as well. The lack of a generally accepted definition and application of resilience extends to electric energy delivery systems. Without an accepted definition, it is difficult to implement programs or processes to improve resiliency. In this paper, existing work from industry, regulatory bodies, and national laboratorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The resilience of an EEDS is described as a characteristic of the people, assets, and processes that make up the EEDS and their ability to identify, prepare for, and adapt to disruptive events (in the form of changing conditions) and recover rapidly from any disturbance to an acceptable state of operation [9]. This definition suggests a few key considerations.…”
Section: Inl Resilience Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The resilience of an EEDS is described as a characteristic of the people, assets, and processes that make up the EEDS and their ability to identify, prepare for, and adapt to disruptive events (in the form of changing conditions) and recover rapidly from any disturbance to an acceptable state of operation [9]. This definition suggests a few key considerations.…”
Section: Inl Resilience Frameworkmentioning
confidence: 99%
“…However, care should be taken so that metrics selected are specific enough to enable decision making, whether for operational or planning purposes. Metrics should ideally aid in direct and indirect assessment of resilience, cover both quantitative and qualitative properties of the system, meet as many of the characteristics shown in Figure 3 as possible, and consider the entire physical and operational scope of the system, including inputs, capacity, capabilities, performance, and outcomes [9].…”
Section: Define System Resilience Goals and Metricsmentioning
confidence: 99%
“…Following an extensive literature review on resilience definitions and metrics, INL defines resilience as: "a characteristic of the people, assets, and processes that make up the EEDS and their ability to identify, prepare for, and adapt to disruptive events (in the form of changing conditions) and recover rapidly from any disturbance to an acceptable state of operation." [2].…”
Section: Resilience Frameworkmentioning
confidence: 99%
“…In INL's literature review of resilience metrics, one key finding suggested resilience metrics could be categorized in three dimensions: resolution, type, and maturity [2]. That second dimension, type, breaks metrics down into five categories: inputs, capacities, capabilities, performance, and outcomes [11].…”
Section: Metricsmentioning
confidence: 99%
See 1 more Smart Citation